Hepatic Pathology among Patients without Known Liver Disease Undergoing Bariatric Surgery: Observations and a Perspective from the Longitudinal Assessment of Bariatric Surgery (LABS) Study - Kleiner, David E.; Berk, Paul D.; Hsu, Jesse Y.; Courcoulas, Anita P.; Flum, David; Khandelwal, Saurabh; Pender, John; Pomp, Alfons; Roerig, James; Machado, Laura L.; Wolfe, Bruce M.; Belle, Steven H.; null (Seminars in Liver Disease, 2014)
Liver biopsy is not routine during bariatric surgery. Alanine aminotransferase (ALT) is widely used to screen for liver disease. We assessed the relationship between ALT and pathology in biopsies from Longitudinal Assessment of Bariatric Surgery (LABS) patients with normal preoperative ALTs. Biopsies from the LABS-1 and LABS-2 studies were scored using the NASH CRN and Ishak systems. Diagnosis and histology were examined in relation to alanine aminotransferase (ALT) values. Six-hundred ninety-three suitable biopsies were evaluated. Biopsied patients had a median age of 45 years; 78.6% were female and 35.1% diabetic; median body mass index was 46 kg/m2. Six-hundred thirty-five biopsied patients had preoperative ALTs. Median ALT was 25 IU/L (interquartile range [IQR] 19–36 IU/L); 26.6% had an ALT > 35 IU/L and 29.9% exceeded the more restrictive Prati criteria for normal. Using the Prati criteria, 7.9% of participants with normal ALT had steatohepatitis and 5.3% had ≥ stage 2 fibrosis. Logistic regression models were used to predict the probabilities of having bridging fibrosis/cirrhosis or a diagnosis of borderline/definite steatohepatitis in the unbiopsied LABS-2 sample. The proportion of biopsied participants with these findings was very similar to the modeled results from the unbiopsied cohorts. We estimated that 86.0% of participants with advanced fibrosis and 88.1% of participants with borderline/definite steatohepatitis were not biopsied and went undiagnosed. As ALT did not reliably exclude significant obesity-related liver disease in bariatric surgery patients, consideration should be given to routine liver biopsy during bariatric surgery and medical follow-up of significant hepatic pathology.
Keywords: bariatric surgery; liver biopsy; NAFLD; steatohepatitis; cirrhosis